How Close Are Macro-Economics/Macro-Thermodynamics? The Knowledge & Energy Pair: Economics in the Net Zero Era - Hemmat Safwat (Athens Journal of Business & Economics)
The paper has two academics Parts (Themes in the Paper’s Title); the first addresses several common features that relate to the theoretical bases of the two discipline Macro-Economics and Macro-Thermodynamics, the second Part is underlining the paradigm that the author proposed in 2022 (the knowledge-energy “KE” pair) that is present in all activities encountered in any enterprise. In Part I, the author elaborates on two new terms in Macro - Economics; Income Potential Function “IPF”, Labor Effort “LE”, that were introduced in 2002 through his work with Professor Dr. Ibrahim M. Oweiss. Innovations represent a key factor in deriving the developments of both nation’s economies and electrical power systems. Part I opens new areas for generalization of theories in Macro-Economics based on established theoretical treatments in Macro-Thermodynamics. In Parts I&II, many applications from Economics and Thermodynamics that exhibit similar trends are cited supporting the close relation of the first part of the Paper’s title. The novel concept of the KE pair in part II could lead to a knowledge measurement scale. Part III summarizes takeaways from Parts I&II. In Part IV, with the ideas and thinking behind the contents of Parts I&II, factoring his expertise in energy the author summarizes important considerations for stakeholders & economists dealing with nation’s economies to meet the big challenges facing countries in the energy transition / decarbonization / Net Zero Era by 2030 and 2050. Relatively short times to transform the energy infrastructure that was built over more than a century (for many countries).